Reviewed book: Investigaciones fenomenológicas. Author: Guillermo Hoyos Vásquez - Vargas Guillén, Germán (Estudios de Filosofía, 2012)
The Colección Fenomenología, of the Biblioteca de Ciencias Sociales y Humanidades, Editorial Siglo del Hombre, was created 4 years ago. However, only in 2012 appears, with its three first books. The object of it is to present systematically the intellectual trajectory of the scholars in the discipline, with its dialogues. Thus, the collection makes with this book a task that must be evaluated in relation to the dialogues that are linked, implicitly and explicitly, with other works - by Klaus Held, based on the same series.